African Politics in Comparative Perspective - Goran Hyden (Cambridge University Press, 2006)
This 2006 book reviews fifty years of research on politics in Africa. It synthesizes insights from different scholarly approaches and offers an interpretation of the knowledge accumulated over the years. It discusses how research on African politics relates to the study of politics in other regions. It focuses on such key issues as the legacy of a movement approach to political change, the nature of the state, the economy of a location, the policy deficit, the agrarian question, gender and politics and ethnicity and conflict. It ends by reviewing what scholars agree upon and what the accumulated knowledge offers as insights for more effective political and policy reforms. This book is for undergraduate and graduate courses in African and Comparative Politics as well as development-oriented courses in Political Science and related disciplines. It is also of great relevance to governance and development analysts and practitioners in international organizations.